2011
DOI: 10.1136/gut.2011.239301.423
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes following an initial unsuccessful colonoscopy: a 5-year complete audit of teaching hospital colonoscopy practice

Abstract: Introduction Unless the full colon is adequately visualised at colonoscopy there is a risk of missing signifi cant pathology including advanced neoplasia and colorectal cancer (CRC). Incomplete colonoscopy occurs in 10%, and while the reasons for failure are well described, overall outcomes of these patients are not. These patients may be subjected to a second investigation or left partially investigated. The aim of this study was to determine the eventual patient outcomes following their initial failed colono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…[27][28][29] Inadequate bowel preparation was the most common reason for incomplete colonoscopy, accounting for nearly 25% of failed colonoscopies, in a 5-year complete audit of colonoscopy practice in a teaching hospital in the United Kingdom. 30 Never the less, crude colonoscopy completion rates did increase significantly from 66% in 2004-2008 to 79% in 2009-2013 and adjusted completion rates from 80% in 2004-2008 to 95% in 2009-2013. Published colonoscopycompletion rates vary substantially ranging from 76% to 99%.…”
Section: -2008 2009-2013mentioning
confidence: 93%
“…[27][28][29] Inadequate bowel preparation was the most common reason for incomplete colonoscopy, accounting for nearly 25% of failed colonoscopies, in a 5-year complete audit of colonoscopy practice in a teaching hospital in the United Kingdom. 30 Never the less, crude colonoscopy completion rates did increase significantly from 66% in 2004-2008 to 79% in 2009-2013 and adjusted completion rates from 80% in 2004-2008 to 95% in 2009-2013. Published colonoscopycompletion rates vary substantially ranging from 76% to 99%.…”
Section: -2008 2009-2013mentioning
confidence: 93%
“…It is estimated that 10%‐20% of colonoscopies performed are incomplete or inadequate examinations with either the inability to intubate the caecum and/or inability to adequately inspect the mucosa . The most common cause of an incomplete colonoscopy is poor bowel preparation (BP) …”
Section: Introductionmentioning
confidence: 99%
“…4 The most common cause of an incomplete colonoscopy is poor bowel preparation (BP). 5 Poor BP precludes the ability to properly visualise the colonic mucosa, thereby leading to failed detection of a neoplasm. Chokshi and colleagues found that among those patients who underwent repeat colonoscopy after an initial colonoscopy with inadequate BP and no polyps seen, 31% had at least one adenoma detected on their repeat study.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 The bowel preparation required for colonoscopy is often the part of this procedure that patients find most difficult, 12 and failure to complete it results in loss of procedural accuracy. 10,13,14 There is also a small miss rate of colonoscopy for colorectal neoplasia, as demonstrated by tandem colonoscopy studies. 15 …”
mentioning
confidence: 99%